Neoplasia in Cri du Chat Syndrome from Italian and German Databases. (24th April 2017) - Guala, Andrea; Spunton, Marianna; Kalantari, Silvia; Kennerknecht, Ingo; Danesino, Cesare
Abstract : Cri du Chat syndrome (CdC) is a chromosomal abnormality (deletion of short arm of chromosome 5) associated with intellectual disability and typical anatomical abnormalities. Research up to now focuses on the management of the disease during childhood. The longer lifespan of these patients warrants deeper investigations of how and if aging could be affected by the syndrome. We decided to focus on the association of the disease with proliferative disorders. Data on proliferative disorders in a cohort of 321 patients from Italian and German Cri du Chat databases were collected. A neoplasia was present in four patients (age 10–50 yrs), and a fifth patient developed a cholesteatoma during childhood. It is of interest that two cases had an early onset of the neoplasia as compared to the expected age of development in the general population. The chromosome region deleted in 5p does not contain genes whose haploinsufficiency is a well-known main cause of the proliferative disorders observed. We nonetheless believe that reporting even sporadic cases of proliferative disorders in CdC patients may increase our knowledge as to the natural history of the disease. In conclusion, available information suggests that surveillance for cancer development in CdC can follow the guidelines for the general population.